Synthesis of 2-Amino-5-aryl-1,3,4-thiadiazolopeptides as Potent Antitubercular Agents - Asif, Karigar; Himaja, M.; Ramana, M.V.; S. Sikarwar, Mukesh (Asian Journal of Chemistry, 2012)
A novel series of 2-amino-5-aryl-thiadiazole analogs of amino acids and dipeptides were synthesized using 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide as coupling agent and N-methyl morpholine (NMM) as base. Structure of all the newly synthesized compounds was confirmed by IR, 1H NMR, 13C NMR and mass spectral data. All the synthesized compounds were screened for their antitubercular, antibacterial and antifungal activity.